United we restrain, divided we rule: Neoliberal Reforms and Labor Unions in Turkey and Mexico - Basak Kus; Isik Ozel (European Journal of Turkish Studies, 2010)
This article explores the variation in state policy toward labor unions in the context of neoliberal market reforms by cross-examining the cases of Turkey and Mexico. Although taming the power of unions so as to decrease resistance to market reforms and increase labor market flexibility remained a somewhat common objective to the neoliberal agenda across nations, governments understood “labor’s challenge” in different ways, due to their nations’ distinct histories of unionization, and utilized different strategies and means to deal with it. We show that such differences help explain why the union movement in Turkey has become more centralized and concentrated in the neoliberal era, while the union movement in Mexico has become more fragmented and decentralized.